Pain as a risk factor of depression and anxiety symptoms with multiple myeloma during maintenance therapy - Shi, Hui; Ren, Honglin; Tian, Ying; Chen, Zhe; Xu, Cuiping; Lu, Lu; Ma, Xiaoyu; Li, Xiaoyan; Chen, Wenming; Guo, Tong; Fan, Cuizhen; Gao, Wen (Frontiers in Psychology, 2022)
Objective To investigate the prevalence of depression or anxiety in patient with multiple myeloma (MM) in China during maintenance treatment and its associated influencing factors. Methods Patients with MM (n = 160) received maintenance therapy, and control subjects (without MM, n = 160) matched on age, sex, and BMI were recruited. Patients completed questionnaires, including the Patient Health Questionnaire-9 (PHQ-9), the Generalized Anxiety Disorder 7-item Scale (GAD-7), and the Verbal Pain Rating Scale (VPRS). Data on the Clinical characteristics, biochemical indicators of de novo MM were from the database of the Hematology Department of Beijing Chao-yang Hospital. Multiple linear regression model analysis was used to compare the differences in PHQ-9 and GAD-7 scale scores between the control group and the case group after correction for relevant variables. Multiple logistic regression models were subsequently used to analyze the correlation between the presence or absence of anxiety and depression and clinical indicators in the MM groups. Results Depression symptoms was present in 33.33% and anxiety symptoms in 24.68% of first-episode MM in the maintenance phase of treatment, and depression symptoms in the index-corrected MM group was significantly different from that in the control group (t = 2.54, P < 0.05). Analyses of multiple logistic regressions: biochemical indicators and clinical typing were not significantly associated with anxiety and depression. Compared to the pain rating 1, the risk of depressive mood was greater in the case group with the pain rating 2 (OR = 2.38) and the pain rating ≥ 3 (OR = 4.32). The risk of anxiety was greater in the case group with the pain rating ≥ 3 than the pain rating 1 (OR = 2.89). Conclusion Despite being in clinical remission, depressive mood problems in patients with MM remain prominent. Clinicians should enhance mood assessment and management in patients with concomitant pain.